Kecurangan Akuntansi (Fraud Accounting) Dalam Perspektif Islam - Yurmaini Yurmaini (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2017)
Fraud is unmeasurable false because fraud is like mistakes, with the factors inside the mistakes. The fraud accounting is the wrong view from the material facts in the financial report or journal. The wrong message can be delivered to share holders or creditors, or inside the organization to cover the incompetence, or cover financial disguise or cheating by the staff, agent etc. The cheating by the outsider such as seller, supplier, contractor, consultant or customer with double invoicing, giving the lower quality material, over credit limit or the misvalue of the goods. Accounting fraud in the view of Islam is the unacceptable action. Some fraud in accounting in the view of Islam : Ghulul, Risywah (bribe), Ghasab (take others property), Sariqah (stealing), Rihabah (robbery), Al-Maks (unidentified fee), Al-Ikhtilas (pick pocket), dan Al-Ihtihab.Keywords: fraud, accounting, cheating